Exploring the potential of audio-tactile messaging for remote interpersonal communication - Brown, Lorna; Krishnan, Renan; Sellen, Abigail; Harper, Richard (Proceedings of CHI 2009, 2009)
Shake2Talk is a mobile messaging system that allows users to send sounds and tactile sensations to one another via their mobile phones. Messages are created through gestures and then sent to the receiver’s phone where they play upon arrival. This paper reports a study of the Shake2Talk system in use by six couples, and begins to uncover the types of messaging practices that occur, and the values and meanings that users ascribe to these messages.